The impact of bank regulatory changes, bank specific factors, and systematic risk upon the off-balance-sheet activities in selected conventional commercial banks in South Asia - Basheer, Muhammad Farhan (2020)
Risk diversification is among the crucial issue’s conventional banks face. The banking system in South Asia -, which is a diversified banking system, compriseding of local and foreign banks , is also engaged in off-balance sheet activities. Therefore, the prime objective of the current study is to investigate the impact of bank-specific factors, bank regulatory changes and systematic risks on the off-balance sheet activities in conventional commercial banks of selected countries in South Asia namely Bangladesh, India, Pakistan and Sri Lanka . Based on the research objectives, the study employeds two estimates, namely, fixed effects (FE) (time and country) and generalized method of momentum GMM (difference). Within the FE static methodology, the researchers estimated structure, comprising both country and time fixed effect in order to further account for financial shocks and other time-related events that affect each of the four countries. The majority of the findings show consistency with the market power theory, which indicates that the banks in South Asia consider the risks arising from the off-balance sheet activities and performance, as key determinants of off-balance sheet activities engagement. Banks in South Asia are also inclined to follow the market regulatory and tax theory, which claims that the increasing regulatory requirements in the form of capital requirement, provides banks with incentives to take excessive risks of off-balance sheet activities. The systematic risks arising from the macroeconomic factors also appear as a significant determinant of the off-balance sheet activities. The findings of the study have several practical implications that can be applied in the context of the bank-specific risks, regulatory pressure from regulatory restructuring and risks from the systemic factors. These implications are of great importance and will help the policymakers and practitioners to understand the issues related to the off balance sheet activities.